Distinct petrographic responses to basin reorganization across the Triassic–Jurassic boundary in the southwestern Barents Sea - Line, Lina Hedvig; Müller, Reidar; Klausen, Tore Grane; Jahren, Jens; Hellevang, Helge (Basin Research, 2020)
A general shift towards higher mineralogical and textural maturity changes the reservoir character across the Triassic–Jurassic transition in the southwestern Barents Sea basin (SWBSB), largely affecting the hydrocarbon prospectivity in the region. Petrographic and geochronological provenance data presented in this paper suggest that the shift from mineralogically immature to mature sandstones initiated during the deposition of the Norian–Rhaetian Fruholmen Formation, and varies with basin location. Strong contrasts between the Fruholmen Formation and underlying formations are associated with proximity to the rejuvenated Caledonian and Fennoscandian hinterlands and are mainly restricted to the southern basin margins. In the basin interior, subtle petrographic variations between the Fruholmen Formation and older Triassic sandstones reflect a distal position relative to the southern hinterland. The long‐lived misconception of a regional compositional contrast in the Arctic at the turn of the Norian can be attributed to higher sampling frequency associated with hydrocarbon exploration activity along the southern basin margins, and masking by increased annual precipitation and subsequent reworking during the Jurassic. Geothermal signatures and rearrangement of ferric clay material across the Carnian–Norian transition support a recycled origin for the Fruholmen Formation in the basin interior. As the closest tectonically active region at the time, the Novaya Zemlya fold‐and‐thrust belt represents the best provenance candidate for polycyclic components in Norian–Rhaetian strata. In addition to recycling in the hinterland during the Late Triassic, local erosion of exposed intrabasinal highs and platforms at the Triassic–Jurassic transition represents a second process where thermodynamically unstable mineral components originally sourced from the Uralides may be removed. Textural and mineralogical modification may also have occurred in marginal‐marine depositional environments during periods with elevated sea level. ...